2022
DOI: 10.3390/cancers14235728
|View full text |Cite
|
Sign up to set email alerts
|

The TLK1–MK5 Axis Regulates Motility, Invasion, and Metastasis of Prostate Cancer Cells

Abstract: Background: Metastatic dissemination of prostate cancer (PCa) accounts for the majority of PCa-related deaths. However, the exact mechanism of PCa cell spread is still unknown. We uncovered a novel interaction between two unrelated promotility factors, tousled-like kinase 1 (TLK1) and MAPK-activated protein kinase 5 (MK5), that initiates a signaling cascade promoting metastasis. In PCa, TLK1–MK5 signaling might be crucial, as androgen deprivation therapy (ADT) leads to increased expression of both TLK1 and MK5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The first RNAPII-bound region is located between the genes TLK1 and METTL8 at 40 kb and 44 kb, respectively ( Figure 7 B). TLK1 has been linked to poor patient outcomes in multiple cancer types, including GBM 39 and prostate cancer metastasis, 40 , 41 and it is involved in DNA replication and chromatin assembly. 39 METTL8 has been identified as a potential biomarker in hepatocellular carcinoma, 42 and high levels have been associated with improved patient survival in pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The first RNAPII-bound region is located between the genes TLK1 and METTL8 at 40 kb and 44 kb, respectively ( Figure 7 B). TLK1 has been linked to poor patient outcomes in multiple cancer types, including GBM 39 and prostate cancer metastasis, 40 , 41 and it is involved in DNA replication and chromatin assembly. 39 METTL8 has been identified as a potential biomarker in hepatocellular carcinoma, 42 and high levels have been associated with improved patient survival in pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
“…7c ). TLK1 has been linked to poor patient outcomes in multiple types of cancer, including Glioblastoma Multiforme 39 and Prostate cancer metastasis 40,41 , and is required for DNA replication and chromatin assembly 39 . METTL8 has been identified as a potential biomarker in Hepatocellular carcinoma 42 , and high levels have been linked to patient survival in Pancreatic cancer 43 .…”
Section: Resultsmentioning
confidence: 99%
“…There are ongoing efforts to develop TLK1 and TLK2 inhibitors for targeting cancer cells with their promising roles in maintaining genome stability (64)(65)(66). Emerging evidence demonstrated that TLK1 and TLK2 are involved in cancer progression and therapeutic resistance (67)(68)(69)(70) and it has been shown that inhibition of TLK potentiates cell-killing in different types of cancers (1,(70)(71)(72)(73)(74), making TLK 1 and 2 attractive targets for therapeutic strategy development.…”
Section: Discussionmentioning
confidence: 99%